Correlates of autonomic nervous system function in a general population with special reference to HbA1c: The Nagahama study. (May 2020) - Takahashi, Naomi; Takahashi, Yoshimitsu; Tabara, Yasuharu; Matsumoto, Takeshi; Kawaguchi, Takahisa; Kuriyama, Akira; Ueshima, Kenji; Matsuda, Fumihiko; Chin, Kazuo; Nakayama, Takeo
Abstract: Aims: As the glucose tolerance of patients with diabetes worsens, autonomic nervous system (ANS) function decreases. Only a few studies, using plasma glucose, have reported on this relationship in large general populations that include people with wide range of glycemia. This study aimed to examine correlates of ANS function with special reference to HbA1c which is more stable than plasma glucose among community residents. Methods: Spectral analysis was performed to assess heart rate variability (HRV) using 1-minute electrocardiogram RR interval data recordings from 7690 residents aged 35–79 years in Nagahama City, Japan. HRV parameters were log-transformed. Multiple regression analysis was performed using potential correlates. Results: lnLF decreased with age (regression coefficient, −0.025; P < 0.001), BMI (−0.010; P = 0.035), and HbA1c (−0.068; P = 0.036). lnHF decreased with age (−0.029; P < 0.001), BMI (−0.032; P < 0.001), and HbA1c (−0.173; P < 0.001). lnLF/HF increased with age (0.003; P = 0.002), BMI (0.023; P < 0.001), and HbA1c (0.105; P < 0.001). Women showed lower lnLF and lnLF/HF than men. Sleep quality assessed by the Pittsburgh Sleep Quality Index, smoking and drinking had almost no relation. Conclusions: Although the associations were weak, age, BMI and HbA1c were inversely correlated with parasympathetic activity, while positively correlated with sympathetic activity among general residents.